2013
DOI: 10.1590/0037-8682-0125-2013
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and CD4 cell counts in patients with HIV/AIDS receiving antiretroviral therapy

Abstract: Introduction: Even with current highly active antiretroviral therapy, individuals with AIDS continue to exhibit important nutritional defi cits and reduced levels of albumin and hemoglobin, which may be directly related to their cluster of differentiation 4 (CD4) cell counts. The aim of this study was to characterize the nutritional status of individuals with human immunodefi ciency virus/acquired immunodefi ciency syndrome (HIV/AIDS) and relate the fi ndings to the albumin level, hemoglobin level and CD4 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
4
21
3
Order By: Relevance
“…According to the Joint United Nations Program on HIV/AIDS (UNAIDS) report in sub-Saharan Africa six in 10 adults living with HIV are currently woman [1]. The present study was also in agreement with the UNAIDS report.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…According to the Joint United Nations Program on HIV/AIDS (UNAIDS) report in sub-Saharan Africa six in 10 adults living with HIV are currently woman [1]. The present study was also in agreement with the UNAIDS report.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies showed the introduction of HAART greatly improved the life expectancy and quality of life; however malnutrition is still a concern [1,6]. Despite this fact, there was no any statistically significant association between CD4 cell count and the malnutrition indicators used in this study.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations